Examining the effectiveness of bike fitting - Bini, R. R.; Hume, P. (Sports Medicine, 2025)
Bike fitting is the detailed process of evaluating the cyclist`s physical and performance requirements and abilities and systematically adjusting the bike to meet the cyclist`s goals and needs [1]. A clear definition of bike fitting has not yet been agreed upon but the assumed process involves optimising posture and movement through changes in the bicycle and in the posture of the cyclist [2]. These changes can involve replacing components of the bicycle (e.g. saddle) or altering the position of the handlebar and saddle or the foot attachment to the pedals.